Pengaruh Model Context-Based Learning Berbantuan Simulasi PhET terhadap Keterampilan Berpikir Kritis pada Materi Elastisitas dan Hukum Hooke - Fadilah, Evi; Al Farizi, Taufiq; Suartini, Kinkin (Jayapangus Press, 2024)
The main focus of this research is centered on the issue of low critical thinking skills among high school students, particularly in the study of elasticity and Hooke's law. The research aims to investigate how a context-based learning model with the assistance of PhET simulations influences students' critical thinking skills in the context of elasticity and Hooke's law. The study was conducted at SMAS Cengkareng 1 Jakarta for five weeks in October 2023, involving a sample of 30 students. The sample selection utilized purposive sampling, comprising 30 students from class XI MIPA B (control group) and class XI MIPA A (experimental group). The applied design was quasi-experimental with a Nonequivalent Control Group Design. Data collection involved a critical thinking test instrument consisting of twelve essay-type questions (validated with a validity of 0.86 and reliability of 0.83). The results of the posttest hypothesis test using the t-test at a significance level of 0.05 showed a sig.(2-tailed) value of 0.000, with the conclusion H0 rejected (indicating the influence of the context-based learning model with PhET simulation assistance on students' critical thinking skills). The critical thinking of the experimental group showed a greater improvement (N-gain 0.459 in the moderate category) compared to the control group (N-gain 0.288 in the low category). The implications of this research encourage educators to implement learning models to enhance low critical thinking skills, allowing students to actively engage with complex challenges related to real-life contexts. The study underscores the need to improve critical thinking skills across various subjects.